2020
DOI: 10.21203/rs.3.rs-88143/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis of structures and characteristics of the SPL gene family in wheat (Triticum aestivum L.)

Abstract: Background: The SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) genes encode a family of plant-specific transcription factors that contain a conservative SBP domain. SPL proteins play important roles in plant growth and development, such as plant architecture, flowering regulation, and grain yield. However, the systematic analysis of TaSPL gene family in wheat is lacking.Results: In this study, 56 TaSPL genes were identified from wheat genome and divided into eight groups (G1-G8), according to the phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(146 reference statements)
0
0
0
Order By: Relevance
“…Our research has revealed that 22 CDPK genes are present in A. duranensis, while 23 CDPK genes are found in A. ipaensis (Table S4). Notably, previous research identified 35 CDPK genes in each of these wild peanuts, but only through the BLASTP method [59]. This implies that our approach is more effective.…”
Section: Discussionmentioning
confidence: 95%
“…Our research has revealed that 22 CDPK genes are present in A. duranensis, while 23 CDPK genes are found in A. ipaensis (Table S4). Notably, previous research identified 35 CDPK genes in each of these wild peanuts, but only through the BLASTP method [59]. This implies that our approach is more effective.…”
Section: Discussionmentioning
confidence: 95%